Microbial Profile and Antibiotic Susceptibility of Organisms in Bile Cultures from Patients Undergoing Endoscopic Retrograde Cholangiography: A Cross-Sectional Study from a Tertiary-Care Center in Nepal - Shrestha, Swarup; Basnet, Bhupendra K.; Khanal, Ajit; Poudyal, Nandu S.; Poudel, Mukesh S. (Journal of Gastrointestinal Infections, 2025)
Acute cholangitis, a potentially life-threatening biliary infection, frequently arises from biliary obstruction. Prompt diagnosis and appropriate antimicrobial therapy are critical to preventing sepsis and reducing mortality. Empirical antibiotic selection requires an understanding of local microbial profiles and resistance patterns.This study aims to describe the microbial profile and antibiotic resistance patterns in bile cultures obtained from patients undergoing endoscopic retrograde cholangiography (ERC) at a tertiary-care teaching hospital in Kathmandu, Nepal, and assess if there is a difference in prevalence rates between these groups.This cross-sectional study was conducted at a tertiary-care teaching hospital in Nepal between November 2023 and April 2024. A total of 88 patients (44 with acute cholangitis and 44 without) undergoing ERC were included. Bile samples were aseptically collected, cultured, and analyzed for microbial identification and antibiotic susceptibility. Statistical analysis was performed with a two-tailed two-sample proportion z-test to compare bile culture positivity and microbial patterns between groups.Of the 88 patients, 74 (84%) had positive bile cultures, with a significantly higher prevalence in the cholangitis group (93%) compared with those without cholangitis (75%, p = 0.041). Gram-negative organisms predominated, with Escherichia coli (38%), Citrobacter (30%), and Klebsiella (19%) being the most common. Pseudomonas species were isolated exclusively in the cholangitis group. Antibiotic resistance rates were high, including multidrug resistance among Pseudomonas and Enterobacter isolates.This study highlights the high prevalence of gram-negative pathogens in ERC patients with cholangitis, emphasizing targeted empiric therapy and antimicrobial stewardship.
Keywords: acute cholangitis; endoscopic retrograde cholangiography; antibiotic resistance; Nepal